Analytic philosophy of history of Arthur Danto: paradoxes of historical knowledge (Actual Problems of Mind, 2022)
Abstract: The paper claims that Arthur Danto's conception of analytic philosophy oh history is the first systematic attempt of analytic analyzing the historical knowledge, its limits and possibilities of knowing the past. The author emphasizes that Danto presents a post-positivist approach to solving epistemological issues of history, so his philosophy oh history might be considered as the result of a successful rethinking of a narrow positivist approach to science.In Analytical Philosophy of History Danto clearly divides the philosophy of history into the substantive philosophy of history, aimed at describing “all history”: all past and all future, and analytic philosophy of history, which is aimed at investigating issues of historical knowing. Conceptions of substantive philosophy of history assert of being theories of history, they often use historical research texts as simply factual material foe their speculative constructions. Substantive philosophy of history is deeply criticized by Danto as a mistaken mode of thinking about the past that unjustified extrapolates the narrative structures of historical narrative into the future and predicts (and narrates) events before they happen. A historian can make predictions about certain events in the past and discover them as a result if his or her predictions were correct, but history deals only with the past.It is stressed that Danto distinguishes and analyzes a number of “paradoxes” of historical knowledge, caused both by historians' lack of knowledge  of the trends in the development of modern science, and by the lack of understanding of the real problems of historical knowing in the contemporary philosophy of science. For example, this applies to the issue of unobservability of subject-matter, which is more the rule than the exception for modern sciences, therefore it cannot pose any exceptional epistemological problems for history. This also applies to the issue of theoretical and value loading of historical knowledge. Danto calls it the Bacon's mistake to believe that a scientist or historian starts their research with the study of “pure” facts, they both need theoretical training to begin their investigation at all. History as a science is characterized by that feature, according to which a historian, as Danto soundly proves, often knows more and better about the events he or she studies than the participants or witnesses of these events.
Keywords: Key worlds: philosophy of history, analytic philosophy of history, narrative, narrative sentence ideal chronicle, temporal wholes.